Effectiveness of Implementing Home Ownership Kredit Restructuring in Efforts to Reduce Problem Loans (Case Study of Bank BTN KC Sukabumi) - Putri Widya Cahyani; Elan Eriswanto (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Since its founding in 2017, Bank BTN KC Sukabumi has succeeded in maintaining its credit quality from non-performing loans with an NPL percentage of 0%, but in March 2023, NPLs began to appear with a percentage of 0.03%. This research aims to determine the effectiveness of implementing home ownership credit restructuring in an effort to reduce non-performing loans at Bank BTN KC Sukabumi. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The research results show that the implementation of credit restructuring at Bank BTN KC Sukabumi follows POJK guidelines Number 40/POJK.03/2019 which includes six main stages, namely debtor mapping, application submission, document verification, analysis, approval and monitoring. Even though various strategies have been implemented such as early identification, evaluating debtor criteria, determining restructuring patterns that are appropriate to the debtor's condition, and post-credit restructuring guidance, data as of June 2024 shows that the percentage of Special Mention Collectibility (DPK) is 15.49% and Non-Performing Loans are 3.52%, exceeding the maximum ideal limit set by the bank internally. Measuring effectiveness using Sondang P. Siagian's theory and historical comparison of NPL percentages shows that the implementation of credit restructuring at Bank BTN KC Sukabumi has not been effective in reducing problem loans, with an increase in NPL from 0.03% in March 2023 to 3.52% in June 2024. Causes of ineffectiveness include long-term economic impacts, factory closures resulting in layoffs, and an imbalance between the number of problem debtors and the capacity of the collection team. Even though the bank has increased the number of officers in March 2024, the effectiveness of the collection team is still not optimal.